Davidson's Principles & Practice of Medicine - Edited by Nicholas A. Boon: Nicki R. Colledge and Brain R. Walker (New Delhi Churchill Livingstone, 2006)
Since it was first published this comprehensive text has met the requirements of several generations of medical students preparing for their examinations, while serving as a valuable reference for doctors in training. Includes a revised chapter Principles of Medical Psychiatry concentrating on the important aspects of major psychiatric illness as it relates to medical practice and a new chapter on the Principles of Critical Care Medicine brings together the major conditions that are handled in the ITU. The major manifestations of disease are color-coded throughout and indexed through a contents list on the inside cover.
Include Illustration and Index
Keywords: Internal medicine -- Medicine